2021
DOI: 10.1080/09537287.2021.1903279
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and eliminating waste in Engineer-To-Order (ETO) projects: a multiple case study

Abstract: This article explores how waste reduction approaches as found in lean thinking can be applied to engineering design in Engineer-To-Order (ETO) projects based on a multiple case study of ten companies over a 2-year period. ETO projects deliver capital goods that are customised to individual customer requirements. Customisation and ultimately value generation are achieved through an iterative engineering design process. Although inevitable, iterative engineering design allows much leeway for waste generation, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 54 publications
2
10
0
5
Order By: Relevance
“…This can be now extended to study how practitioners use many information sources and knowledge assets (if available) when reaching for artefact synthesis within the project delivery without NPD. This study strengthens the observations regarding benefits of lean in capital goods (Birkie et al, 2017) and lean flows done by (Adlin, 2022;Jünge et al, 2021) and the practitioners reported good experiences having defined processes for different module flows.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This can be now extended to study how practitioners use many information sources and knowledge assets (if available) when reaching for artefact synthesis within the project delivery without NPD. This study strengthens the observations regarding benefits of lean in capital goods (Birkie et al, 2017) and lean flows done by (Adlin, 2022;Jünge et al, 2021) and the practitioners reported good experiences having defined processes for different module flows.…”
Section: Discussionsupporting
confidence: 88%
“…It supports productivity and aims to reduce iteration in engineering design. Lean approach and waste types are studied in Engineering-to-order (ETO) context (Birkie et al, 2017;Birkie and Trucco, 2016;Jünge et al, 2021). ETO operations performance was sustained with the integrated lean implementation.…”
Section: State Of the Artmentioning
confidence: 99%
“…There is a strong connection between the outcomes of this investigation and the performance of construction projects in terms of sustainability, considering the environmental, economic, and social perspectives [30,31]. The dissemination of industrialized building systems can be regarded as an important strategy for achieving sustainable construction by bringing several benefits, such as the increase in productivity [32], improvement in safety and working conditions [31], short delivery time [33], higher reliability in terms of quality [34], and energy and waste reduction [35,36]. Dallasega and Rauch [30] suggested that the positive impact of industrialized construction on sustainability is directly related to the implementation of some core production management concepts and principles, such as limiting the amount of WIP throughout the supply chain and synchronizing processes carried out by different stakeholders.…”
Section: Introductionmentioning
confidence: 83%
“…The LC Methodology seeks the identification and elimination of waste found on site; all activities that generate high variability and do not generate value to the work should be eliminated from the process; in addition, it should be noted that the LC methodology is increasing in popularity and more and more companies are implementing it; although, in a slower way compared to its impact on other industries [1]- [4]. Countries always looking for innovation in the construction sector, such as China, the United States, Singapore, and Japan, are some of the countries that are at the forefront of using methodologies that improve the productivity and quality of their final products [5].…”
Section: Introductionmentioning
confidence: 99%